Application of Bioactive Coatings Based on Chitosan for Soybean Seed Protection. (31st May 2012) - Zeng, Defang; Luo, Xinrong; Tu, Renjie
Abstract : Soybean seeds suffer attacks of various pests that result in a decreased yield in northeastern China. Until recently, people use pesticides such as insecticides to achieve the goal of controlling pests. Chitosan extracted from deacetylation of chitin is promising candidates as a seed-coating agent to control agrotis ypsilon, soybean pod borer, and soybean aphid effectively. An experimental study on influences of chitosan with different concentrations on pest controlling and soybean growth was made in the paper. Coating based on chitosan was used as a feeding deterrent and for enhancing the germination and quality of soybean seeds. Results indicated that all chitosan coating had a significant effect on antifeeding against pests; with the increasing concentration, antifeedant rate (AR) were increased obviously, especially when in the concentration of 5%, santifeedant rate of agrotis ypsilon, soybean pod borer, and soybean aphid reached 82.89%, 87.24%, and 80.21%, respectively. Also chitosan coating increased seed germination, plant growth, and soybean yield efficiently, especially when, in the concentration of 5%, the yield was increased by about 20% compared with CK. The application of chitosan in soybean seed coated is an appropriate option to control pests replacing high-toxicity pesticides and enhance soybean yield.